Dinamika Karakteristik Curah Hujan Harian Wilayah Gambut Sumatera Kaitannya dengan El Niño Southern Oscillation (ENSO) dan Indian Ocean Dipole (IOD) - Muhammad Irfan; Khairul Saleh; Nety Kurniawati (Postgraduate, University of Mataram, 2025)
Sumatran peatlands constitute a highly vulnerable ecosystem strongly Sumatran peatlands are a vulnerable ecosystem highly sensitive to daily rainfall variability driven by large-scale climate modes such as El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD). This study analyzes the frequency distribution and intensity of daily rainfall over Sumatran peatlands from 1995 to 2023 in relation to ENSO and IOD phases. Daily rainfall data from nine BMKG stations were analyzed using Probability Density Function (PDF), supported by monthly climatology and Fast Fourier Transform (FFT) spectral analysis. Results show a right-skewed rainfall distribution, with peak frequency below 20 mm/day. During El Niño and positive IOD events, the PDF shifts leftward, indicating increased dry days; during La Niña, the right tail extends, increasing extreme rainfall probability. FFT reveals dominant annual cycles and sub-seasonal signals linked to the Madden-Julian Oscillation. Spatial patterns are consistent, though inland stations show stronger responses than coastal ones. Despite the lack of seasonal stratification and formal significance testing in this preliminary analysis, findings highlight how ENSO and IOD alter rainfall risk—drought during warm phases and flooding during cold phases. These insights support the development of early warning systems and climate-informed peatland management policies